ROLETA (ROEMAH LELE TARIKAN): UPAYA PEMBERDAYAAN PEREMPUAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT MELAUI DIVERSIFIKASI PRODUK OLAHAN IKAN LELE BERBASIS DIGITAL MARKETING - Qorry Ambiya; Siti Nur Asiah; Nur Ngafiah (Nusantara Hasana Journal, 2023)
The village in Kumpeh Ulu District, Muaro Jambi Regency, namely Tarikan Village, is a village that has potential in the fisheries sector, especially in terms of catfish farming. Therefore, supported by the potential and opportunities that already exist, the KSPM UNJA Pro Idea team intends to create a multiplier effect from the existence of this cultivation through further processing of catfish so as to produce finished products that have high selling value. This is due to the absence of assistance and further training regarding catfish processing and the lack of public knowledge that catfish is not only sold conventionally but can also be processed into finished products so that it can be business oriented in the future through training and assistance regarding the processing of catfish-based products so that they become products. flagship in Tarikan Village by diversifying products. On the other hand, the team will implement a digital marketing strategy starting from social media marketing to build brand awareness as well as a product promotion medium.